Making and Unmaking. - Lomax, Jenni; Olowu, Duro; Higgie, Jennifer; Jhaveri, Shanay (Ridinghouse : Londen, 2016)
Achaintre, Caroline ; Adams, Marina ; Agbodjelou, Leonce ; Albers, Anni ; Amini, Tasha ; Anderson, Hurvin ; Apfelbaum, Polly ; Armstrong Jones, Tony ; Bahabba, Emheyo ; Beshty, Walead ; Boetti, Alighiero ; Bourgeois, Louise ; Bove, Carol ; Brice, Lisa ; Brown, James ; Buckman, Zoe ; Cahun, Claude ; Clark, Lygia ; Conderelli, Céline ; CorvMora, Tommaso ; Frampton, Meredith ; Fujiwara, Simon ; Gallaccio, Anya ; Hajjaj, Hassan ; Hicks, Sheila ; Huddleston, Dona ; Itter, Diane ; Julien, Isaac ; Kenlock, Neil ; Mack, Eric ; McDonald, Peter ; McMillian, Rodney ; Maiga, Hamidou ; Macropoulos, Ari ; Marden, Brice ; Milan Wardell ; Mukherjee, Mrinalini ; Mutu, Wangechi ; Neel, Alice ; Nqaba, Nobukho ; Ofili, Chris ; Ové Cbe, Horace ; Penn, Irving ; R, Tal ; Roberts, Michael ; El-salahi, Ibrahim ; Shonibare, Yinka ; Sidibé, Malik ; Simpson, Lorna ; Sinsel, Daniel ; Soulou, Christiana ; Tanning, Dorothea ; Taylor, Henry ; Vandenberg, Al ; Yiadom-Boakye, Lynette, Yamada, Masaaki ; Wiley, Kehinde
tentoonstellingscatalogus naar aanleding van"Making and Unmaking, Camden Arts centre, London, 19 Juni - 18 september 2016
boek